Robust image watermarking against geometric attacks - Dong, Qi (2013)
The recent progress in digital multimedia technologies has offered many facilities in transmission, reproduction and manipulation of digital contents. However, this advance in technology has also brought the problems such as copyright protection and ownership verification. One of the proposed solutions to such problems is digital watermarking. In the design of a robust watermarking scheme, the most important requirement is robustness. For image watermarking, improving the robustness against geometric attacks is one of the challenges in the field of digital watermarking. Thus, the work presented in this thesis is concerned with the design of robust image watermarking schemes against geometric attacks as well as image processing operations.